Ab Initio Study of Spectroscopic Constants and Anharmonic Force Field of Hypochlorous Acid $HO^{35}Cl$ (Journal of Atomic and Molecular Sciences, 2015)
The molecular geometries, spectroscopy constants, and anharmonic forcefield of hypochlorous acid have been calculated at B3PW91, MP2, CCSD(T) levels oftheory employing three basis sets, 6-311g(3df,2p), 6-311g(3df,3pd) and cc-pVQZ, respectively.The equilibrium structures, rotational constants, anharmonicity constants,vibration-rotation interaction constants, quartic and sextic centrifugal distortion constantsare compared with the available experimental data. Coriolis coupling constantsare also calculated here. The partial spectroscopy constants show that the MP2 representan improvement over the results obtained from B3PW91. The CCSD(T) method isalso a good choice to study the anharmonic force field of this molecule.
Keywords: Anharmonic force field; spectroscopy constant; Ab initio study; hypochlorous acid.